Administration of Levetiracetam via Subcutaneous Infusion for Seizure Control in the Palliative Care Setting: A Narrative Review - Fern Beschi; Rachel Hughes; Jennifer Schneider (MDPI AG, 2024)
This narrative review aims to summarise the information available on the use of subcutaneous (SC) levetiracetam (LEV) in the adult palliative care setting using clinical texts, databases, journals, and grey literature. A search strategy utilising Embase, Medline CINALH and Cochrane databases, as well as Google Scholar, was conducted with the mapped search terms "levetiracetam", "subcutaneous" and "palliative". LEV intravenous (IV) proprietary products are used subcutaneously, including as continuous subcutaneous infusions (CSCIs), in the adult palliative care setting. The total LEV daily dose ranged from 250 mg to 5000 mg and LEV was administered with various diluents at varying volumes. The data identified a clinical desire to mix LEV with other medications; however, the current evidence on combination compatibility is observational only and drug stability in combinations is lacking. The majority of information in the literature on SC LEV use is based on case reports and retrospective audits. Case reports, whilst at times offering more clinical detail, represent specific circumstances not necessarily applicable to a larger patient cohort. The findings of retrospective audits are limited by the documentation and detail reported at the time of patient care that may not be designed for data collection.